MORPHOFUNCTIONAL EVALUATION OF MACULAR-FOVEAL CAPILLARIES: A Comparative Optical Coherence Tomography Angiography and Microperimetry Study. Issue 7 (July 2020) - Pilotto, Elisabetta; Leonardi, Francesca; Deganello, Davide; Convento, Enrica; Midena, Edoardo; Frizziero, Luisa
Abstract : Purpose: To analyze the macular function of eyes with macular-foveal capillaries (MFC), a condition characterized by the absence of the foveal avascular zone (FAZ), identified by optical coherence tomography angiography. Methods: Eight eyes with MFC at optical coherence tomography angiography and normal visual acuity were consecutively recruited. Eight eyes of healthy subjects were enrolled as healthy controls. All eyes underwent optical coherence tomography, optical coherence tomography angiography, best-correct visual acuity, low-luminance visual acuity, contrast sensitivity measurement, colour vision tests, and both mesopic and scotopic microperimetry. Results: Best-corrected visual acuity, low-luminance visual acuity, contrast sensitivity, and colour vision tests did not differ between the two groups. At mesopic microperimetry, both foveal retinal sensitivity and mean mesopic retinal sensitivity of the central 1° were statistically inferior in MFC versus control eyes ( P < 0.0001 and P < 0.0001, respectively). At scotopic microperimetry, a dense foveal scotoma, normally present in control eyes, was completely lacking in MFC eyes. Scotopic foveal retinal sensitivity was statistically superior in MFC versus control eyes ( P = 0.009). Conclusion: The absence of the foveal dense scotoma in scotopic conditions underlines that the foveal rod-free zone is not present when capillaries are present in this area. An anomalous foveal distribution of photoreceptors, with both rods and cones present in this area, may be postulated in MFC eyes. Abstract : Macular function of eyes with macular-foveal capillaries is characterized by an abnormal mesopic and scotopic foveal function suggesting an abnormal distribution of both photoreceptors (rods and cones) in these eyes.